2008
DOI: 10.1002/marc.200700725
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar ‘Reptational’ Movements of Single Synthetic Polymer Chains on Substrate Observed by AFM

Abstract: Peculiar ‘reptational’ movements of isotactic PMMA chains on mica are observed by in situ AFM. The polymer molecules comprise long flexible chains that exhibit reptative, or snake‐like, motion on the substrate along the direction of the polymer chain. Intriguingly, some chains underwent forward then backward motion in which the head of the chain moved in a curvilinear manner along the previous contours of the polymer chain. No limitation in the direction of movement for the ends of the polymer chain was antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
(12 reference statements)
1
12
0
Order By: Relevance
“…In previously described systems with reptational movements the obstacles were distributed randomly. [27][28][29] In contrast, molecular lamellas on graphite have a linear geometry and well dened symmetry, which causes the observed peculiarities of DNA movement on molecular nanotemplates on graphite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously described systems with reptational movements the obstacles were distributed randomly. [27][28][29] In contrast, molecular lamellas on graphite have a linear geometry and well dened symmetry, which causes the observed peculiarities of DNA movement on molecular nanotemplates on graphite.…”
Section: Resultsmentioning
confidence: 99%
“…25 One of the main advantages of this method is the possibility to study the dynamics of adsorbed DNA molecules in solutions. [26][27][28][29] The purpose of this work was to achieve deeper understanding of controlled DNA immobilization, assembly and organization on molecular nanotemplates of stearylamine and stearic acid on HOPG using an AFM dynamical study in liquid. We have characterized DNA conformation on these nanotemplates in solution and explored DNA segmental movement in real time during several tens of minutes.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The idea of inducing the motion of nano-objects by means of such periodic response of a polymer system to cyclic variation of the vapour environment was explored. 6 Recently, such experiments were achieved at the singlemolecule level: vapour-induced reptational movement 7,8 and reversible conformational transitions (collapse and re-extension) 9,10 of single flexible polymer chains on mica were observed in real-time. But in spite of this progress with single chains, bottle-brush-like macromolecules 11 still remain potentially more convenient systems for direct SFM observation in real time during repetitive conformational changes induced by cyclic exposure to vapours of different nature.…”
Section: Introductionmentioning
confidence: 99%
“…26 We also reported that the movement of isolated it-PMMA chains deposited on mica under high humidity could be observed in situ by AFM; the chains moved along their length similar to "reptational movements" on the substrate under high humidity. 27,28 The effect of the scanning AFM tip on the movements was proven to be negligible by several evidence, the most important one of which was that the observed movements of the chains during an interruption of the scanning were comparable to the movements during the scanning. We also visualized the crystallization behavior of an it-PMMA amorphous monolayer on mica into folded-chain crystals under high humidity in situ at the molecular level.…”
Section: Introductionmentioning
confidence: 99%